Адміністративно-правові засади профілактичної діяльності підрозділу внутрішньої безпеки : автореферат дисертації - Болілий, О. П.; Bolilyi, O. P.; Іванцов, В. О. - науковий керівник (Харківський національний університет внутрішніх справ, 2024)
У дисертації наведено теоретичне узагальнення та нове вирішення наукового завдання, яке полягає у визначенні сутності, змісту та розкритті особливостей адміністративно-правових засад профілактичної діяльності підрозділу внутрішньої безпеки, розробленні на цій основі науково обґрунтованих пропозицій та рекомендацій щодо вдосконалення адміністративного законодавства. Аналізуються методологічні засади правового регулювання профілактичної діяльності підрозділу внутрішньої безпеки. Характеризується адміністративно-правовий статус підрозділів внутрішньої безпеки як суб’єкта профілактичної діяльності. Визначаються напрями удосконалення адміністративно-правового забезпечення профілактичної діяльності підрозділу внутрішньої безпеки.

Thesis provides a theoretical generalization and a new solution to the scientific task of defining the essence, content and disclosure of the specific features of the administrative and legal framework for preventive activities of internal security units, and on this basis, developing scientifically sound proposals and recommendations for improving administrative legislation. It has been argued that preventive activity is one of the direct tasks of internal security units, which is carried out in the process of: 1) implementation of the mechanism for combating offences among police officers; 2) removal of obstacles to the performance of their official duties, which are exclusive in nature and also comply with the Constitution and laws of Ukraine. In turn, it has been proposed to divide the functions of internal security units into two groups, namely: the first group includes the functions of combating offences committed by police officers, civil servants and other police officers who violate the obligations established by law to properly perform their duties and impartially observe the rights and freedoms of citizens, and therefore such functions are aimed at preventing internal systemic discredit of the NPU; the second group consists of functions to prevent negative influence on the NPU employees by other persons, to counteract external discredit of the National Police and its officials. It has been proven that preventive activities are an essential element of the practical activities of internal security units. It is implemented in: a) anti-corruption activities of these units; b) counteracting (preventing) police officers from committing actions that infringe on human rights and freedoms, such as violation of the principle of equality, unlawful imposition of physical restrictions, physical or moral violence by police officers; c) ensuring compliance with the special legal regime of access to information and office premises, etc. The author has established that prevention is a complex organizational and legal phenomenon which covers a system of administrative and legal measures aimed at: 1) identifying the causes and conditions of offences committed by police officers, civil servants and police officers themselves, as well as by entities which may impede their work, including by disseminating deliberately false information with a view to discrediting the NPU; 2) neutralizing the impact of these factors on the effective implementation of the NPU's tasks. It has been substantiated that the peculiarities of preventive activities of internal security units as an object of administrative and legal regulation are: a) permanent in nature; b) carried out using appropriate forms and methods clearly defined by legal provisions; c) such activities are carried out on the basis of relevant analytical data; d) such preventive activities simultaneously combine various measures to achieve an optimal result; e) in accordance with the methods established by law, interact with those entities whose legal status covers the implementation of preventive measures to counter offences in the NPU. The author has determined that the administrative and legal status of internal security units as a subject of preventive activities is derived from the administrative and legal status of the National Police as a whole. It characterises the legal position of these units in the NPU system and their role in ensuring its activities. Its peculiarities are manifested in a number of specific elements that together define the role of internal security units in ensuring the functioning of the National Police in a way that allows it to fulfil its purpose effectively and impartially  to protect human rights and freedoms, combat crime, and maintain public safety and order. The elements of the respective status include: the purpose (elimination of causes and conditions of offences among NPU employees, as well as minimization of factors that create unlawful obstacles to their activities); tasks and functions, competence and powers that allow for the implementation of functional tasks; guarantees of their activities (e.g. legal (availability of a regulatory framework governing the activities of such units); organizational; financial and economic, etc.).
Administrative and legal principles of preventive activities of the internal security unit
Keywords: Україна; Автореферати дисертацій. Abstracts of Theses. Авторефераты диссертаций; 12.00.07; підрозділи внутрішньої безпеки; Національна поліція; профілактична діяльність; повноваження; компетенція; законність; дисципліна; контроль; юридична відповідальність; воєнний стан; адміністративне законодавство; internal security units; National Police; preventive activities; powers; competence; legality; discipline; control; legal responsibility; martial law; administrative legislation; Ukraine